Fields of vision : essays on the Travels of William Bartram - Braund, Kathryn E. Holland, 1955-; Porter, Charlotte M., 1948- (University of Alabama Press, 2010)
A classic work of history, ethnography, and botany, and an examination of the life and environs of the 18th-century south. William Bartram was a naturalist, artist, and author of Travels through North and South Carolina, Georgia, East and West Florida, the Cherokee Country, the Extensive Territories of the Muscogulees, or Creek Confederacy, and the Country of the Choctaws. The book, based on his journey across the South, reflects a remarkable coming of age. In 1773, Bartram departed his family home near Philadelphia, Pennsylvania, as a British colonist;